A hybrid two‐stage modular DC–DC converter with zero‐voltage switching. (30th March 2021) - Nazih, Yousef; Hossam‐Eldin, Ahmed; Elserougi, Ahmed
Abstract: Conventional modular multilevel converters (MMCs) are widely used in high power applications due to their various astonishing advantages; however, they fail to achieve balanced capacitor voltage in DC operation. In this paper, a hybrid two‐stage modular DC–DC converter is proposed to solve the issue of unbalanced capacitor voltages. The proposed converter consists of a single‐phase half‐bridge MMC with half‐bridge submodules followed by a medium voltage valves‐based H‐bridge rectifier. The proposed converter is used in medium‐voltage applications such as feeding a DC‐load or interconnection between two DC grids of different voltage levels. The proposed configuration achieves successful DC–DC conversion with a low number of switches, a high conversion ratio with bidirectional power flow, low current stresses, soft switching across the second stage, and low switching losses. The operational concept and the control algorithm have been illustrated in detail. Finally, the effectiveness of the proposed DC–DC converter is evaluated based on simulation studies of MATLAB SIMULINK and a scaled‐down laboratory experimental test rig. Abstract : A new two‐stage hybrid modular DC–DC converter is proposed, where the high voltage valves in the second stage are operated under zero voltage switching to enhance the converter efficiency and to implement the high voltage valve simply by series‐connected switches.